Determinación de las competencias organizacionales en la microempresa Garrigamb S.A del cantón Jama - MERA LOOR, FIAMA ALEJANDRA (2022)
The development of this research aimed to determine the organizational skills in the GARRIGAMB S.A. microenterprise, based on a field and bibliographic methodological procedure, which allowed the development of the three phases of the study, based on the diagnosis of the current state of the organization, through the application of an interview and its characterization with the elaboration of the respective technical sheet. Consequently, in phase two, the organizational competencies were defined, through the application of the expert method, to structure the diagnostic tool (survey), and to carry out the respective treatment of the information collected, its processing, tabulation, and generation analysis; afterwards, through the results obtained, propose an action plan through the 5w + 1h matrix. Regarding the results obtained, a total of nine organizational competencies were established, which according to the results, present a high level of compliance, enjoying an acceptable competitive profile in terms of efficiency, planning capacity, teamwork, monitoring of quality, commitment, responsibility, technology, negotiation and health control, allowing the conclusion of the study in the existence of the need to establish permanent assessment criteria regarding the competitive profile of the institution and given the absence of historical data